2010
DOI: 10.1159/000272025
|View full text |Cite
|
Sign up to set email alerts
|

Distal and Proximal Resource Influences on Economic Dependency among the Oldest Old

Abstract: tenarians were not more dependent than octogenarians. Cognitive ability had the strongest effects for medical care and caregiving services. 'Extraversion', 'ideas', 'neuroticism', and 'competence' personality factors had significant effects for caregiving types and total hours of care received. Conclusion: Monitoring and intervention to maintain cognitive ability are critical practices for autonomy and reduced economic dependency among the oldest old. Psychological resources are more important influences on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…More specifically, in accordance with Rautio et al (2001), those centenarians indicating that they could not meet their expenses had the highest rate of errors on the SPMSQ. Perceptions of how well money took care of needs were inversely related to ability to perform activities of daily living was consistent with other studies as well (e.g., MacDonald et al, 2010;Poon et al, 2010;Rautio et al, 2001). Finding that having a better perception of economic circumstances was related to being less depressed was in line with Chou and Chi (2002).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…More specifically, in accordance with Rautio et al (2001), those centenarians indicating that they could not meet their expenses had the highest rate of errors on the SPMSQ. Perceptions of how well money took care of needs were inversely related to ability to perform activities of daily living was consistent with other studies as well (e.g., MacDonald et al, 2010;Poon et al, 2010;Rautio et al, 2001). Finding that having a better perception of economic circumstances was related to being less depressed was in line with Chou and Chi (2002).…”
supporting
confidence: 89%
“…Johnson (2004) identified financial strain and the rising cost of food as impacting the health of the oldest old via their ability to access healthy food. Several studies have linked socio-economic factors with physical and mental capacity among older adults (e.g., MacDonald et al, 2010;Poon et al, 2010;Rautio et al, 2001). Similarly, Chou and Chi (2002) found that both financial strain and self-rated health were linked with depression, while Rautio et al (2001) identified a positive association between one's perceived financial situation and functional capacity.…”
Section: Relating Adls Cognition and Depression To Perceived Econommentioning
confidence: 99%
“…Economic dependency is addressed using as outcomes proxy reports on participants' income assistance, number of medical care events, number of care-giving types and total care-giving hours [15] . Thus, again both proximal care and distal variables are considered as contributors to the economic dependency of very old adults.…”
mentioning
confidence: 99%
“…MacDonald, Aneja, Martin, Margrett, and Poon (2010) found in their study of Georgia octogenarians and centenarians that increasing age, decreasing cognitive status, decreasing extraversion, and a high level of openness to ideas predicted higher usage of caregiving services. This indicates that at least certain groups of older adults are using care services, but there may be some problems with current care services.…”
Section: Home Care Utilizationmentioning
confidence: 96%
“…A study of Georgia octogenarians and centenarians and near centenarians (MacDonald et al, 2010) found that living in a nursing home, having lower cognitive status, being more neurotic, and having higher competence were all predictors of caregiving hours.…”
Section: Home Care Utilizationmentioning
confidence: 99%